Transformasi Alat Musik Celempung ke Dalam Format KONTAKT Library Sebagai Media Kreativitas Musik Digital - Wilky Leonady; Iwan Gunawan; Toni Setiawan Sutanto; Sailendra Bedantara Gunawan (Program Studi Pendidikan Musik FBS UNP, 2025)
Objective: This study aims to develop a virtual celempung instrument based on the KONTAKT Library as an innovative tool for digital music creation, while also supporting the preservation of Sundanese cultural heritage in the digital age. Method: The research adopts a practice-based research method, which recognizes artistic practice as a legitimate source of knowledge. The process includes pre-production, production, and post-production stages, involving sound sampling, audio editing, and programming through both artistic and technological approaches. It also explores the potential integration of artificial intelligence (AI) in sound design. Results and Discussion: The developed virtual celempung instrument successfully replicates the authentic sound characteristics of the original instrument while offering opportunities for the creation of adaptive and innovative new sounds in cross-genre digital music. The combination of sampling technology and local cultural practice creates an innovative space for the development of tradition-based digital musical instruments. Conclusion: This study contributes to the field of digital ethnomusicology through a novel approach that integrates traditional musical heritage with advanced technologies, particularly AI. The innovation not only enhances access to traditional instruments but also strengthens the synergy between cultural tradition and technological advancement in contemporary music landscapes.